Refinements of Generic Algebraic Inequalities with Application - Chesneau, Christophe; Bagul, Yogesh J. (Journal of Nepal Mathematical Society, 2024)
In this paper, we give alternative proofs and refinements of two generic inequalities due to Bagul and Dhaigude in 2022. As a result, Huygens-type inequalities are established. Illustrations are given to support the main results.